The Timeliness of Basic Immunization in Infants Related To The Knowledge About Covid-19 - Brivian Florentis Yustanta; Layudha Ikhrima (Procedia of Social Sciences and Humanities, 2021)
During the covid-19 pandemic, many parents are worried about providing basic immunizations for their infants. This caused the basic immunization coverage at Gandusari Public Health Service in Blitar Regency in April 2020 to decrease by 4.9%, and in May 2020 to decrease by 19.7%. This study objective to determine the correlation of knowledge about covid-19 and the timeliness of basic immunization in infants. This research was analytic correlational with cross sectional study approach. The independent variable was knowledge about covid-19, while the dependent variable was the timeliness of basic immunization in infants. The population were all parents who had infants as many as 87 parents. This study using simple random sampling. The sample size was 71 parents. The instruments were maternal and child health book and questionnaires. The data were analyzed using chi square test. The results showed that p value 0.001 < 0.05 that there were any correlation of knowledge about covid-19 and the timeliness of basic immunization in infants. The sufficient knowledge of parents about covid-19 made parents hesitate to immunize their infants. Providing basic immunization to infants during a pandemic is not prohibited as long as they comply with health protocols.